Financial comptroller in public procurement. A review of the public works contracts of the Venezuelan state (2020)
This research evaluates the financial and administrative contracting methodology carried out in the period 2012-2013 by the Venezuelan National Government, through one of the public companies destined for urban development for the public sector. The administrative files (32 contracting procedures transactionally) of the selection processes carried out in the period 2012 and 2013, framed by the current legislation for public procurement in Venezuela, were also reviewed and analyzed the financial statements. audited applying the theories of (Díaz & Ramos, 2019; González-Díaz, Lara, López, & Hernández-Royett, 2016; González-Díaz & Perez, 2015). It is concluded that there is a directly proportional relationship in the companies benefiting from the award and that they presented a negative trend in the financial field (horizontal analysis) with the termination or termination, not to the satisfaction of works contracts. Keywords: Public procurement, financial evaluation, urban development, contracting processes. JEL Classification: D92, E62, G3. Received: 05/07/2019.  Accepted: 16/06/2020.  Published: 30/06/2020.